Clinical and epidemiological aspects of leprosy in the elderly - Miranda, Priscilla Ingrid Gomes; Vieira, Chrystiany Plácido de Brito; Araújo, Telma Maria Evangelista de; Araújo, Olívia Dias de; Cardoso, Jonas Alves (Revista Prevenção de Infecção e Saúde, 2022)
Introduction: In the last few decades the number of elderly people in Brazil has presented a significantly increase and comorbidities as leprosy directly impacted their health. Aim: To evaluate the clinical and epidemiological aspects of the leprosy in the elderly population in municipalities with high endemicity in the state of Piauí, from 2001 to 2014. Outlining: Transversal study with 206 new cases of leprosy as from 60 years old, living in Picos and Floriano in the 2001 to 2014 period, notified in the Information System for Notifiable Diseases. Results: the average age was 71 years old, 52.9% was male, 39.3% did not attend to school, 58.7% received up to two minimum wages, 49% of the participants were ranked as multibacillary, 29,1% presented the clinical form borderline and 49% with zero-degree functional disability. It was verified statistically significant association of the degree of physical disability with the living municipality and dyslipidemia and between leprosy reactions and gender, being male increased the chances of having a leprosy reaction by 5.54 times. Implications: The study highlighted that the leprosy represents serious health problem for the elderly and suggests the need for control and surveillance actions through public policies.